Dissimilarities in auditory tuning in midwife toads of the genus Alytes (Amphibia: Anura). (14th May 2015) - Penna, Mario; Velásquez, Nelson A.; Bosch, Jaime
<x xml:space="preserve">Abstract</x> The auditory sensitivity in three species of the anuran genus Alytes (Alytidae) was examined to determine patterns of intra‐ and interspecific variation, relating these measurements to behavioural preferences measured in previous studies and to the adaptive and evolutionary significance of this sensory function. The audiograms obtained with multi‐unit recordings in the torus semicircularis of 13 Alytes cisternasii, 10 Alytes obstetricans, and eight Alytes dickhilleni show two regions of enhanced sensitivity, between approximately 100–500 and 1200–2400 Hz, with minimum thresholds at approximately 40 and 45 dB SPL, respectively. The mean and range of the high‐frequency region differed among species, although the sensitivity, measured as minimum thresholds, was similar. The region of high‐frequency sensitivity was centred at approximately the frequency of the advertisement call in A. cisternasii but, in A. obstetricans and A. dickhilleni, was centred at frequencies higher than the conspecific calls. These results contrast with preferences for lower frequencies exhibited by Alytes in female phonotactic and in male evoked vocal responses. Such loose relationships between signals and receivers suggest that the divergence of the sound communication system in Alytes has implied environmental and phylogenetic factors in addition to sexual selection processes.